2021
DOI: 10.1002/eahr.500091
|View full text |Cite
|
Sign up to set email alerts
|

Advance Research Directives: Dementia Researchers' Views on a Prototype Directive and Implementation Strategies

Abstract: Advance research directives (ARDs) enable people to document preferences for future research participation in the event of incapacity. This article reports on interviews with 11 dementia researchers in Australia that focused on the content of a prototype ARD and processes for making and using ARDs. Participants agreed that an ARD template should provide information to explain research and the rationale for making a directive, allow the person to nominate trusted individuals to be involved in future decisions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…The findings from the present study contribute new perspectives on promotion and documentation of advance research planning. Our participants advocated multifaceted measures to raise awareness of advance research planning by reaching people through their interactions with health, aged‐care, legal, and government entities, strategies similar to ones endorsed by dementia researchers 37 . Promotion of advance research planning could also be integrated into initiatives that connect prospective participants and researchers, such as dementia or other research registries 38 and outreach by community health workers 39 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings from the present study contribute new perspectives on promotion and documentation of advance research planning. Our participants advocated multifaceted measures to raise awareness of advance research planning by reaching people through their interactions with health, aged‐care, legal, and government entities, strategies similar to ones endorsed by dementia researchers 37 . Promotion of advance research planning could also be integrated into initiatives that connect prospective participants and researchers, such as dementia or other research registries 38 and outreach by community health workers 39 …”
Section: Discussionmentioning
confidence: 99%
“…Our participants advocated multifaceted measures to raise awareness of advance research planning by reaching people through their interactions with health, agedcare, legal, and government entities, strategies similar to ones endorsed by dementia researchers. 37 Promotion of advance research planning could also be integrated into initiatives that connect prospective participants and researchers, such as dementia or other research registries 38 and outreach by community health workers. 39 Participants in this study received an ARD form and an accompanying guidance booklet designed to assist their understanding of health-related research, with a focus on dementia research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the workshop, participants received the following materials as preparatory reading: a workshop agenda; brief participant biographies; a sample advance research directive form and an accompanying guidance booklet (see Appendix S1). The latter documents were developed as part of earlier work (led by authors NR, EM and BJ) with input from dementia researchers 11 and consumers aged 50 and older with interests in dementia research. (The consumer interview study is reported in a separate research article that is under review).…”
Section: Methodsmentioning
confidence: 99%